Inter-comparison exercise utilizing x- and γ-ray spectrometry - Pappa, Filothei K.; Tsabaris, Christos; Patiris, Dionisis; Eleftheriou, Georgios; Androulakaki, Effrossini G.; Kokkoris, Michael; Vlastou, Roza (HNPS Advances in Nuclear Physics, 2020)
Radionuclides are characterized by their nuclear and chemical behavior. Additionally, the geochemical characteristics of radionuclides result in their accumulation in the sediments via sorption processes. In this work the radionuclide activity concentrations obtained by gamma-ray spectrometry (HPGe detector) were converted to metal concentrations as described in [1]. The results were compared with the measured metal concentrations obtained by atomic spectrometry (X-ray fluorescence system-XRF). The samples originate from the coastal environment of two Greek areas, characterized by elevated values of natural radionuclides (e.g. 226Ra) and metals. The preliminary study revealed a good agreement among the concentrations of potassium calculated via activity concentrations of 40K and those of XRF measurement, while a great divergence was observed for the thorium case. These differences can be attributed to the low statistics, as well as to the calibration set-up of Th XRF measurement.